Hexadecane biodegradation of high efficiency by bacterial isolates from Santos Basin sediments. (May 2019) - Ferrari, Vitor B.; Cesar, Augusto; Cayô, Rodrigo; Choueri, Rodrigo B.; Okamoto, Débora N.; Freitas, Juliana G.; Favero, Mariana; Gales, Ana C.; Niero, Cristina V.; Saia, Flavia T.; de Vasconcellos, Suzan P.
Abstract: The aim of the study was the investigation of bacterial diversity from sediments collected at Santos Estuarine System, regarding to their abilities for hexadecane biotransformation. Hexadecane is a medium-chain linear alkane, considered as a model molecule for hydrocarbon biodegradation studies. It is a component from aliphatic fraction of crude petroleum, commonly related to environmental contamination by diesel oil. Santos Basin is an area with historical petroleum contamination. In the present work, sediment samples from this area were inoculated in artificial seawater (ASW), containing hexadecane as carbon source. Six bacterial isolates were selected as resistant to hexadecane. Chromatographic results showed biodegradation indexes above 97%. After 48 h of culture, five of them could degrade >80% of the initial hexadecane added. These isolates were characterized by 16S rDNA gene sequencing analysis. The following species were found: Bacillus amyloliquefaciens, Staphylococcus epidermidis, Micrococcus luteus, Nitratireductor aquimarinus, and Bacillus pumilus . Highlights: Hexadecane as a model molecule for hydrocarbon biodegradation studies. Estuarine sediment as a source of biological solution for environmental cleaning. Bacterial isolates with fast biodegradation activity under hexadecane. Potential of marine microorganisms for biodegradation of organic contaminants. Aliphatic fraction of crude oil associated to environmental contamination by diesel.